Semantic space of the research paper abstract - Mironchuk, Tetiana A.; Odarchuk, Natalia A.; Мірончук, Тетяна Андріївна; Одарчук, Наталія Андріївна (Східноєвропейський національний університет імені Лесі Українки, 2018)
The article explores semantic structure of the abstract of geological research papers (GRPA) and proposes a model of its semantic space. Consideration is given to the functional level. Its semantics is concluded to be built by two segments of content – referential and textual ones. GRPA is defined to be a super-segmental sign of secondary denotation and co-reference, which reflects a complex system of semiotic, semiological, and textual relations between two lingual signs – the research paper and the abstract. GRPA referential semantics is studied via the GRPA semiotic relations and establishes coding, patterning, and indexing functions to frame GRPA semiotic semantics, while also recognizing instrumental, indicatory, identifying, substitution, and compensatory functions to be complementary to the GRPA semiotic nature. GRPA semiological relations establish reportive, referential, and reflective functions to be fundamental to GRPA textual semantics, which is supplemented by informative, visualizing, and educative functions. Informativeness, evidentiality, and credibility are determined to constitute core attributes of the GPRA functional semantics. The descriptors of informative semantics of the texts of academic genres and the GRPA, in particular, are concluded to be the predicates of existence, state, identification, movement, physical and intellectual action, location, and characterization.
Keywords: textual reference; functional semantics; syntactic semantics; academic genre texts; semiotics